A system for work efficiency improvement by user activity analysis and feedback. Issue 1 (September 2020) - Timofeev, Dmitrii; Samochadin, Alexander
Abstract: The efficiency of work processes is an important factor in company success and economic growth. Many companies are still using inefficient processes due to a lack of knowledge or defective implementation. The processes that rely upon intellectual labor, such as software development or management activities, are often undocumented, which makes them difficult for optimization. We present a method of tracking of the psychophysical state and activities of employees and providing them feedback intended to optimize the work process for work efficiency and user well-being. We use recorded traces of the user actions, including the created artifacts, and detect the psychophysical states on the base of data acquired from portable devices, including fitness wrist bands and EEG sensors. The method has been implemented in a hardware and software system whose architecture we describe in this paper. The system has been developed for the software engineering industry, but the method itself applies to other domains as well. We show how to adapt the proposed approach to different types of working environments and business processes. As the efficiency of the work process is a major factor contributing to the industrial and economic modernization, we discuss the ways to apply the method to business processes that are important for the Arctic region of Russia.